Pengaruh Labelisasi Halal, Brand Awareness, dan Viral Marketing Terhadap Keputusan Pembelian Konsumen di Mixue: Studi Kasus pada Pelanggan Muslim Mixue di Surakarta - Sela Pratika Dewi; Ahmad Mardalis (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
he food and beverage industry in Indonesia continues to experience growth amidst various ever-changing market trends. Ice cream is one of the most popular food products in Indonesia. One of the ice cream brands that is currently widely discussed by the community is Mixue ice cream. Consumers who are aware of this brand make Mixue easily remembered and recognized. Technological advancements make it easier for people to obtain and access new viral information. Viral marketing strategies facilitate this brand in introducing itself to consumers and serve as a promotional medium for marketers. The emergence of halal certification provided by MUI for Mixue has a significant influence on Indonesian society due to the majority of its population being Muslims. This research aims to analyze the influence of halal labeling, brand awareness, and viral marketing on consumer purchasing decisions in Mixue, especially among Muslim consumers in Surakarta. This study is a quantitative research type using survey methods. The research technique used is purposive sampling, where the researcher uses their own considerations in selecting the necessary population to provide information that is in line with the research needs. The researcher used primary data in analyzing the data. This method was carried out by distributing questionnaires to the target population and obtaining a sample of 210 respondents. The data processing used was with SPSS Statistics version 26. The results of this study indicate that the halal labeling variable, brand awareness variable, and viral marketing variable significantly influence Muslim consumer purchasing decisions in Mixue simultaneously..